Effect of the metallic cleaning and oxidizing pre-treatments on the corrosion behaviour of sol-gel hybrid coated EN AW-6063 alloy - Fontinha, I. R. (2014)
The effect of alloy surface pre-treatments on the corrosion behaviour of sol gel hybrid coated EN AW 6063 alloy was studied. Five pre-treatments were used: solvent degreasing; alkaline degreasing followed by acid etching; alkaline degreasing followed by alkaline plus acid etching, alkaline degreasing followed by acid etching and oxide growth in boiling water and alkaline degreasing followed by acid etching and anodization. Surface morphology depends on the pre-treatment: SEM/EDS analysis revealed that alkaline plus acid cleaned samples exhibited a very smooth deoxidized surface, while all the others showed a rougher surface covered with an oxide layer. This oxide layer is denser and more homogeneous in the samples subjected to the oxide growth steps. A hybrid sol-gel coating, synthesized from glycidoxypropyltrimethoxysilane (GPTMS) and zirconium n-propoxide (TPOZ) precursors, was applied to the different pre-treated metallic substrate by dip-coating. The corrosion behaviour of the coated samples was evaluated by Electrochemical Impedance Spectroscopy (EIS) and by an accelerated corrosion test. Complementarily to the corrosion study, the adhesion of the hybrid sol-gel coating was evaluated by cross-cut and bend tests. The corrosion tests revealed that the pre-treatments including the oxide growth steps lead to the best protection performance, followed by the alkaline degreasing and alkaline plus acid etching one. However, the latter exhibits the worst adhesive behaviour, attributed to the smoother and deoxidized surface of the substrate.